If a n = ( n 2 n ) − 1 find n → ∞ lim ∣ ∣ ∣ ∣ a n a n + 1 ∣ ∣ ∣ ∣ .
Bonus: Is n = 1 ∑ ∞ a n convergent? If yes, what is the sum?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very well written solution! +1 :-)
n → ∞ lim ∣ ∣ ∣ ∣ a n a n + 1 ∣ ∣ ∣ ∣
= n → ∞ lim ∣ ∣ ∣ ∣ ∣ ( 2 n + 2 ) ! ( n + 1 ) ! ( n + 1 ) ! ⋅ n ! n ! ( 2 n ) ! ∣ ∣ ∣ ∣ ∣
= n → ∞ lim ∣ ∣ ∣ ∣ ∣ ( 2 n + 2 ) ( 2 n + 1 ) ( n + 1 ) ( n + 1 ) ∣ ∣ ∣ ∣ ∣
= n → ∞ lim ∣ ∣ ∣ ∣ ∣ n 2 ⋅ ( 4 + n 6 + n 2 2 ) n 2 ⋅ ( 1 + n 2 + n 2 1 ) ∣ ∣ ∣ ∣ ∣
= 4 1 = 0 . 2 5
What about bonus
The limit being 4 1 is easy enough. As for the series, look at the solutions given here .
Problem Loading...
Note Loading...
Set Loading...
First we see the main problem i.e. for the limit:
n → ∞ lim ∣ ∣ ∣ ∣ a n a n + 1 ∣ ∣ ∣ ∣ = n → ∞ lim ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ( n + 1 2 n + 2 ) ( n 2 n ) ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = n → ∞ lim ( 2 n + 2 ) ! / ( ( n + 1 ) ! ) 2 ( 2 n ) ! / ( n ! ) 2 = n → ∞ lim 2 ( 2 n + 1 ) n + 1 = n → ∞ lim 2 ( 2 + n 1 ) 1 + n 1 = 4 1 = 0 . 2 5
Now, heading onto the more challenging bonus :
Since by ratio test we have already shown that n → ∞ lim ∣ ∣ ∣ ∣ a n a n + 1 ∣ ∣ ∣ ∣ = 0 . 2 5 < 1 , therefore the series converges. Its sum is calculated as follows
n = 1 ∑ ∞ ( n 2 n ) 1 = n = 1 ∑ ∞ ( 2 n ) ! ( n ! ) ⋅ ( n ! ) = n = 1 ∑ ∞ Γ ( 2 n + 1 ) Γ ( n + 1 ) Γ ( n + 1 ) = n = 1 ∑ ∞ ( 2 n + 1 ) ⋅ Γ ( 2 n + 2 ) Γ ( n + 1 ) Γ ( n + 1 ) = n = 1 ∑ ∞ ( 2 n + 1 ) ⋅ B ( n + 1 , n + 1 ) = n = 1 ∑ ∞ ( 2 n + 1 ) ⋅ ∫ 0 1 t n ( 1 − t ) n d t = 2 n = 1 ∑ ∞ ∫ 0 1 n t n ( 1 − t ) n d t + n = 1 ∑ ∞ ∫ 0 1 t n ( 1 − t ) n d t = 2 ∫ 0 1 n = 1 ∑ ∞ n t n ( 1 − t ) n d t + ∫ 0 1 n = 1 ∑ ∞ t n ( 1 − t ) n d t interchanging order of summation and integral by Fubini’s theorem = 2 ∫ 0 1 ( t ( t − 1 ) + 1 ) 2 t ( t − 1 ) d t + ∫ 0 1 ( t ( t − 1 ) + 1 ) t ( t − 1 ) d t = 2 [ 3 ( t 2 − t + 1 ) 1 − 2 t + 3 3 2 arctan ( 3 2 t − 1 ) ] 0 1 + [ t − 3 2 arctan ( 3 2 t − 1 ) ] 0 1 = 2 [ − 2 7 2 ( 3 π − 9 ) ] + [ 3 3 2 π − 1 ] = − 2 7 4 3 π + 3 4 + 3 3 2 π − 1 = 2 7 1 ( 2 3 π + 9 )